Comics as Social Media Criticism of Community Activities Restrictions Enforcement Due to COVID-19 in Indonesia - Vizcardine Audinovic; Rio Satria Nugroho (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
The Government's policy in dealing with COVID-19 cases, namely in the implementation of Community Activities Restrictions Enforcement (PPKM) with various inconsistent rules, has triggered criticism from the public, especially comic artists. Through Instagram, PPKM-themed comics are spread and getting much attention from the public. This study aimed to find out how the use of comics as social criticism in the implementation of PPKM. This study applied a critical metaphor analysis in analyzing the metaphors that appear in voicing the aspirations of opinions and social criticism. The sample selection was based on the comics with the highest engagement from the specified theme. The results showed that 50 comics were criticizing the PPKM policy from 20 accounts. The creators raised six significant metaphors, including PPKM as a prison, PPKM as many types of models, PPKM as a form of greed, Covid-19 is described in social class, the Government is heroes PPKM as a form of arrogance. Criticism with satire and humour has received many likes and comments, increasing the sense of social solidarity. The form of criticism on Instagram cannot be underestimated because it has great power to change government policies. Keywords: Critical Metaphor Analysis; Instagram; Political Comics; PPKM; COVID-19